‘An Incalculable Effect’: Subversions of Heteronormativity - Chambers, Samuel A. (Political Studies, 2007)
The writings of Judith Butler are now canonised in the fields of feminist and queer theory, yet her contribution to politics and her role in the field of political theory remain uncertain. I argue, perhaps uncontroversially, that Butler's is a politics of subversion; I also contend, perhaps more contentiously, that Butler's understanding of subversion only takes clear shape in light of her implicit theory of heteronormativity. Butler's work calls for the subversion of heteronormativity; in so doing her writings both illuminate the general problem of normativity for politics and offer a robust response to that problem. Butler resists the tendency to treat norms as merely agreed-upon standards, and she rebuts those easy dismissals of theorists who would take seriously the power of norms thought in terms of normativity and normalisation. Butler's contribution to political theory emerges in the form of her painstaking unfolding of subversion. This unfolding produces an account of the politics of norms that is needed desperately by both political theory and politics. Thus, I conclude that political theory cannot afford to ignore either the theory of heteronormativity or the politics of its subversion.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; hétéronormativité; judith butler; premier cycle; queer; science politique; science politique et droit; soc2014; subversion; systèmes d'oppressions; thématiques